2009
DOI: 10.3928/01484834-20090610-07
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Transcultural Nursing Through Literature

Abstract: One of the biggest challenges in nursing education is to develop culturally sensitive graduates. Although theory and lecture are appropriate to introduce cultural issues, the application of those skills is limited by the kinds of clinical experiences and patient populations students may treat. Literary works are a rich source of information for nursing. This assignment was created to sensitize the students to the influence of cultural diversity. Students were assigned to read one novel from an approved list an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…2 Based on the literature study, a number of research related to the learning methods for improving the cultural competence of nursing students such as the utilization of literature, integrated teaching material, immersion experience with a diverse culture and also the use of role play and clinical simulation. [3][4][5][6][7] Cultural competency is a set of skills and attitudes which made the nurses possible to work effectively, and culturally sensitive in the cultural context of clients which appropriate with the client's need. In general, the attribute of cultural competency includes cultural awareness, cultural knowledge, and cultural skill.…”
Section: Introductionmentioning
confidence: 99%
“…2 Based on the literature study, a number of research related to the learning methods for improving the cultural competence of nursing students such as the utilization of literature, integrated teaching material, immersion experience with a diverse culture and also the use of role play and clinical simulation. [3][4][5][6][7] Cultural competency is a set of skills and attitudes which made the nurses possible to work effectively, and culturally sensitive in the cultural context of clients which appropriate with the client's need. In general, the attribute of cultural competency includes cultural awareness, cultural knowledge, and cultural skill.…”
Section: Introductionmentioning
confidence: 99%
“…Cultural awareness involves self-exploration of one's own social beliefs and assumptions about self and others, with the aim of clarifying values and potentially revealing social stereotypes and pseudo-facts that have not been explored or questioned previously (Halloran, 2009;Narayanasamy & White, 2005;Waite & Calamaro, 2010). Cultural knowledge "is the process of obtaining cultural information and education in order to understand the worldview of others" (Wilson, 2010, p. 716).…”
mentioning
confidence: 98%
“…Analysis of students' comments showed complaints on the difficult reading level and that assignments took much longer then they had anticipated (Halloran, 2009). Although the book list was phenomenal for enrichment of any culturally focused course, the author did not report quantitative evaluation (Halloran, 2009).…”
Section: Students Read the Spirit Catches You And You Fallmentioning
confidence: 98%
“…Novels were chosen to stimulate students' reflections and increase their self-awareness "knowledge, understanding, and compassion" (Halloran 2009, p. 524). However, the students thought the books encouraged stereotypical thinking, and the faculty found that class management was very difficult because students were at different reading points of reference (Halloran, 2009). Analysis of students' comments showed complaints on the difficult reading level and that assignments took much longer then they had anticipated (Halloran, 2009).…”
Section: Students Read the Spirit Catches You And You Fallmentioning
confidence: 99%
See 1 more Smart Citation